APLIKASI GREEN BUILDING BERDASARKAN METODE EDGE - Rezza Mahendra Putra; Mochamad Agung Wibowo; Syafrudin Syafrudin (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2020)
The world of industrial construction is always developing, thus there are negative impacts arise such as the reduction of free / green land, the use of construction materials originated from natural resources in very large quantities, excessive use of energy, and air pollution. We can actually use the tropical climate in buildings and the environments using the green building concept. The green building concept includes several parts of the construction process such as green initiation (awareness of the green building concept), green design (green building design), green construction (environmentally friendly construction process), green operation & maintenance (green building maintenance). This research is conducted with the aim of analyzing the effectiveness of the application of the green building concept in construction of the buildings. The method used in this study is to compare the total cost of maintenance and impact between buildings categorized as buildings with conventional concepts and buildings with green building concepts. The variables used in this study to include the use of the type of material, monthly electricity costs, and monthly water costs. In processing the data the writer use EDGE software and the results of data processing will show the difference in the total maintenance costs of the two buildings.